Enhancing skill acquisition knowledge and practice design in elite level swimming: Effects of a six-week online coach education intervention - Powell, D.; Wood, G.; Dagnall, N.; Payton, C. (International Journal of Sports Science & Coaching, 2025)
In response to calls for examples from sports settings that highlight successful collaborations between skill acquisition specialists and coaches, this study evaluated the effectiveness of a skill acquisition coach education intervention. After an analysis of practice by a skill acquisition specialist, which provided context to impact learning design, two senior coaches from British Para Swimming with no prior knowledge of skill acquisition principles were observed and interviewed. The intervention harnessed coach experiential knowledge by emphasising development in understanding of theory underpinning three key principles of skill acquisition (i) implicit learning, (ii), focus of attention, and (iii) contextual interference, and encouraging informal and experiential learning between sessions. Following the intervention, coaches had adapted their approach to practice design to incorporate theory-informed techniques. Coach observations and interviews highlighted a range of novel findings in skill acquisition. First, outcomes indicated the use of implicit learning techniques in the form of analogy or metaphor cues can facilitate learning for athletes with intellectual disabilities. Second, coaches reported the learning benefits of utilising external and holistic focus cues in the elite athlete setting. Finally, through an increased understanding of the learning-performance distinction, coaches described the benefits of incorporating contextual interference, which emphasised temporal spacing between learning events. The coaches` interpretation and implementation of skill acquisition theory are discussed with reference to potential avenues of exploration in future research.